Effects of carburization process on the mechanical properties of carburized mild steel - Norfarahanim, Muhamad@Ramli (2013)
Due to the complexity of parameters in carburizing, there has been relatively little work on process variables during the surface hardening process. This work focuses on the effects of carburization process on the mechanical properties of carburized mild steel, at constant temperature, 850°C with different time, 2 hours, 4 hours and 6 hours and quenched in oil. The objectives of this project are to study the influence of carburization process for mild steel and to study the material performance after carburization process. After carburization process, the test samples were subjected to standard test and form the data obtained, ultimate tensile strength and Young’s modulus were calculated. The case hardness of the carburized samples were measure. It was observed that the mechanical properties of mild steels were found to be strongly influenced by the process of carburization. It was conclude that the sample carburized at 850°C soaked for four hours followed by oil quenching were better because they showed the higher ultimate tensile strength at 541.41096 MPa.